Field and laboratory testing in young elite soccer players. Issue 2 (23rd March 2004) - Chamari, K; Hachana, Y; Ahmed, Y B; Galy, O; Sghaïer, F; Chatard, J-C; Hue, O; Wisløff, U
Abstract : Aim: To determine if there are correlations between the physical fitness of young soccer players assessed by field and laboratory testing. Methods: Thirty four male soccer players took part in the study (mean (SD) age 17.5 (1.1) years, height 177.8 (6.7) cm, weight 70.5 (6.4) kg). Maximal oxygen uptake (Vo 2 max ) during treadmill running and vertical jump height on a force platform were measured in the laboratory. Field tests consisted of a soccer specific endurance test (Bangsbo test) and 30 m sprint with 10 m lap times. Results: The Bangsbo test correlated with the lowest velocity associated with Vo 2 max ( v Vo 2 max ; R 2 = 0.55, p<0.001), but not with Vo 2 max . Sprint times at 30 m and 20 m were related to peak extension velocity and peak extension force measured during vertical jumping, but not to vertical jump height per se. The jumping force and velocity could explain 46% of the 30 m sprint performance ( R 2 = 0.46, p<0.001). Conclusion: The Bangsbo test and 30 m sprint test correlate with v Vo 2 max and vertical jump force and velocity respectively. The Bangsbo test does not give a good estimate of Vo 2 max in young soccer players.